2016
DOI: 10.1016/j.yebeh.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant activity of β-caryophyllene against pentylenetetrazol-induced seizures

Abstract: Increasing evidence suggests that plant-derived extracts and their isolated components are useful for treatment of seizures and, hence, constitute a valuable source of new antiepileptic drugs with improved efficacy and better adverse effect profile. β-Caryophyllene is a natural bicyclic sesquiterpene that occurs in a wide range of plant species and displays a number of biological actions, including neuroprotective activity. In the present study, we tested the hypothesis that β-caryophyllene displays anticonvul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(53 citation statements)
references
References 24 publications
4
47
1
1
Order By: Relevance
“…Agonism of CB1 and CB2 receptors by exogenous ligands or endocannabinoids in animal models of MS have demonstrated suppression of pro-inflammatory mediators [38], as well as induction of neuroprotection and immunomodulation [39,40,41,42]. BCP (Figure 1), a dietary functional non-psychoactive CB2 receptor ligand [12,13,14] showed analgesic, anti-inflammatory, anticonvulsant, and neuroprotective effects [15,27,29,43,44,45,46]. Nonetheless, the effects of BCP on immune inflammatory diseases of the CNS, such as MS, have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Agonism of CB1 and CB2 receptors by exogenous ligands or endocannabinoids in animal models of MS have demonstrated suppression of pro-inflammatory mediators [38], as well as induction of neuroprotection and immunomodulation [39,40,41,42]. BCP (Figure 1), a dietary functional non-psychoactive CB2 receptor ligand [12,13,14] showed analgesic, anti-inflammatory, anticonvulsant, and neuroprotective effects [15,27,29,43,44,45,46]. Nonetheless, the effects of BCP on immune inflammatory diseases of the CNS, such as MS, have not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…aucheri are a valuable source of sequiterpenes such as β ‐caryophyllene, caryophellene oxide and cuparene ( Table ). β ‐caryophyllene is a natural bicyclic sesquiterpene with many biological activities such as neuroprotective, anticancer, antioxidant and antimicrobial, anticonvulsant, anti‐inflammatory activity…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33] Although some studies reported that the CB2R agonist beta caryophyllene can be seizure-protective, 29,30 other studies observed either no effect of a CB2R agonist (HU308), 32 or greater seizure severity following administration of the CB2R agonist AM1241. [29][30][31][32][33] Although some studies reported that the CB2R agonist beta caryophyllene can be seizure-protective, 29,30 other studies observed either no effect of a CB2R agonist (HU308), 32 or greater seizure severity following administration of the CB2R agonist AM1241.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Although the cell-specific pattern of CB2R expression in the brain remains controversial, both microglial and neuronal expression have been described. Systemic administration of the CB2R agonist, beta caryophyllene, was shown to protect against acutely induced seizures in mice 29,30 ; however, another study reported that direct brain injection of the CB2R agonist, AM1241, increased seizure severity in rats. 28 The few studies that have directly examined the effect of modulating CB2R activity on seizure susceptibility have yielded inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation